Factors associated with prescription of oral anticoagulation for atrial fibrillation in older people living in care homes in Wales: a routine data linkage study 2003–2018. (3rd October 2022) - Ritchie, L; Harrison, S L; Penson, P E; Akbari, A; Torabi, F; Hollinghurst, J; Harris, D; Oke, O B; Akpan, A; Halcox, J P; Rodgers, S E; Lip, G Y H; et al.
Abstract: Background: Prescription of oral anticoagulants (OAC) is paramount for stroke prevention in people with atrial fibrillation (AF), but treatment decisions in older care home residents are complicated by frailty, multi-morbidity and heightened stroke and bleeding risk. There is a paucity of data on factors influencing the decision to prescribe OAC in this high-risk population who are under-represented in research studies. Purpose: To explore the factors associated with OAC prescription for care home residents aged ≥65 years with AF. Methods: Nationwide retrospective cohort study of people aged ≥65 years entering a care home in Wales between 1 January 2003 and 31 December 2018, using anonymised individual-level electronic health record and administrative data sources available within the Secure Anonymised Information Linkage Databank. Unadjusted and adjusted logistic regression models were used to explore the association between resident characteristics and OAC prescription or non-prescription. Results: Between 2003 and 2018, 14, 493 people with AF aged ≥65 years became new residents in care homes in Wales and 7, 057 (48.7%) were prescribed OAC (32.7% in 2003 compared to 72.7% in 2018), Figure 1. Increasing age and prescription of antiplatelet therapy were associated with lower odds of OAC prescription (adjusted odds ratio [aOR] 0.96 per one year age increase [95% confidence interval, 0.95 to 0.96] and aOR 0.91 [0.84 to 0.98], respectively). Conversely, prior venous thromboembolism (aOR 4.06 [3.17 to 5.20]), advancing frailty (mild: aOR 4.61 [3.95 to 5.38]; moderate: aOR 6.69 [5.74 to 7.80]; severe: aOR 8.42 [7.16 to 9.90]) and year of care home entry in the post-non-vitamin K antagonist oral anticoagulant (NOAC) era from 2011 onwards (aOR 1.91 [1.76 to 2.06]) were associated with higher odds of OAC prescription, Figure 2. Conclusions: The proportion of care home residents prescribed OAC therapy has increased over time with the introduction of NOACs in 2011, but OAC prescription rates are still sub-optimal. Although there is an expected rise in OAC prescribing for increasingly frail people, further work is needed to investigate the interaction with deprivation and other socio-economic and demographic factors to assess potential inequalities in prescribing across these groups. Targeted educational tools for clinicians are needed to address barriers to OAC prescription for AF, such as older age and separate indications for antiplatelet therapy. Funding Acknowledgement: Type of funding sources: None.